Funcionalidad familiar y autoeficacia académica percibida en estudiantes de Educación General Básica de la Unidad Educativa Ecuador de la Parroquia La Unión - López Aguilar, Keny Fabricio (2024)
The general objective of this research is to analyze the relationship between family functionality and perceived academic self-efficacy in students of Basic General Education of the Ecuador Educational Unit of La Unión Parish.. The type of research was descriptive with a non-experimental research design with a quantitative approach. The sample consisted of 60 students between the ages of 8 and 12 years of both sexes, selected through a non-probabilistic sampling by convenience, with a survey technique and the instrument used was the family APGAR questionnaire, which was proposed by Smilkstein in 1978 and has been validated in different populations and the multidimensional scale of child self-efficacy (EMAI), which was developed by Oros in 2004, this scale has been used in different research and contexts to assess self-efficacy in children and adolescents.